Cell cycle regulation of thymidine kinase: residues near the carboxyl terminus are essential for the specific degradation of the enzyme at mitosis. - Kauffman, M G (1991)
The level of human thymidine kinase (TK) polypeptide is subject to cell cycle regulation. The enzyme is barely detectable in G1 phase but increases 10- to 20-fold by M phase. The low level of human TK in G1 phase is due primarily to the specific degradation of the protein during cell division. Substitution of heterologous promoters, removal of the introns, and deletion of all of the 3' untranslated region from the human TK gene do not affect cell cycle regulation of the enzyme. However, deletion of the carboxyl-terminal 40 amino acids or fusion of beta-galactosidase to the carboxyl terminus of human TK completely abolishes cell cycle regulation and stabilizes the protein throughout the cell cycle. These alterations do not significantly alter the specific enzymatic activity of TK. Changing the carboxyl terminus or deletion of the last 10 amino acids does not alter cell cycle regulation. These data demonstrate that residues near the carboxyl terminus of TK are essential for the cell cycle phase-specific degradation of the enzyme.